Project Based Learning Model on Critical Thinking Ability Seen from Cognitive Style in Elementary Schools - Siti Rohana; Apri Irianto; Reza Rachmadtullah (Journal of Education and Teacher Training Innovation, 2023)
The ability to think critically in the 21st century is very important for developing children's thinking ideas. This ability is very likely to be empowered intentionally through the educational process. In this century it is very influential in human life, especially in the field of technology and knowledge. However, students' critical thinking skills are still low, with one of the factors being the learning model which is still considered monotonous. Therefore this study aims to determine the effect of the project based learning model on critical thinking skills seen from cognitive style. The type of research used is quantitative research with research methods using tests and observations, the subjects of this research are 5th grade elementary school students. With the method of data analysis using the normality test, homogeneity and ANOVA hypothesis testing. The data was analyzed quantitatively. The results of this study indicate that there is an influence of the project based learning learning model on students' Critical Thinking abilities in science subjects at SDN Gaungan 02. The project based learning model emphasizes that student activities are in the form of collecting information and using it to produce something useful for the lives of students themselves or for other people, but still related to basic competencies in the curriculum.